Compaction of diagenetically altered mudstones – Part 2: Implications for pore pressure estimation. (November 2016) - Goulty, N.R.; Sargent, C.
Abstract: Diagenetically altered mudstones compact mechanically and chemically. Consequently, their normal compaction trends depend upon their temperature history as well as on the maximum effective stress they have experienced. A further complication is that mudstones are commonly overpressured where clay diagenesis occurs, preventing direct observation of the hydrostatic normal compaction trend. A popular way to estimate pore pressure in these circumstances is to calculate the sonic normal compaction trend in a well with a known pressure–depth profile by applying Eaton's method in reverse, and then to estimate pore pressure in offset wells using Eaton's method conventionally. We tested this procedure for Cretaceous mudstones at Haltenbanken. The results were inconsistent because the sonic log responds differently to disequilibrium compaction overpressure and unloading overpressure, and their relative contributions vary across the basin. In theory, a two-step method using the density and sonic logs could estimate the contributions to overpressure from disequilibrium compaction and unloading. The normal compaction trend for density should be the normal compaction trend at the maximum effective stress the mudstones have experienced, not at hydrostatic effective stress. We advocate the Budge-Fudge approach as a starting point for pore pressure estimation in diagenetically altered mudstones, a two-step method that requires geological input to help estimate the overpressure contribution from disequilibrium compaction. In principle, the Budge-Fudge approach could be used to estimate the normal compaction trend for mudstones at the maximum effective stress they have experienced, and so form the basis of the full two-step method through the use of offset wells. Our initial efforts to implement the full two-step method in this way at Haltenbanken produced inconsistent results with fluctuations in estimated pore pressure reflecting some of the fluctuations in the density logs. We suspect that variations in the mineralogical composition of the mudstones are responsible. Highlights: We introduce the normal compaction surface for diagenetically altered mudstones. Eaton's method gives poor results where overpressure generation mechanisms vary. Separate accounting for disequilibrium compaction and unloading is required. In principle, a two-step method can be implemented using density and sonic logs. The Budge-Fudge approach offers a partial solution and basis for a two-step method.